If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(3n + -4) = 0 Reorder the terms: 8(-4 + 3n) = 0 (-4 * 8 + 3n * 8) = 0 (-32 + 24n) = 0 Solving -32 + 24n = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '32' to each side of the equation. -32 + 32 + 24n = 0 + 32 Combine like terms: -32 + 32 = 0 0 + 24n = 0 + 32 24n = 0 + 32 Combine like terms: 0 + 32 = 32 24n = 32 Divide each side by '24'. n = 1.333333333 Simplifying n = 1.333333333
| 38n=15 | | -6(-3n+5)= | | 2/5x-3=3 | | 2x^2+20x+200=0 | | 1-3x=3x+19 | | 3x+3=-3x-9 | | -5k^2+10k=0 | | -9+6(4y-8)= | | H(x)=Ln(3x-4) | | 0.27m+2=0.35m | | 924=11y+143 | | 1-g+s-2g+3(g-2)=p | | 16t^2-80t-64=0 | | 3+9(-7+4s)= | | y=2(6) | | -56/-7/8 | | p--2=9 | | -5k+10k=0 | | g(x)=4.9t^2+6t+0.4 | | Log(1/2x) | | -20x+10=6+12x | | -3/4x-2=-8] | | -3(-7+2y)-6= | | -38x+7=159 | | (-9ln(x)-6)/(x^2)=0 | | 10=2x(8)+b | | 12s-s=22 | | -32x=-4 | | 3x=(x*x)-40 | | 18/6d-9=1/6 | | p=2k-2w | | 3X+5X-8=15-X |